Conceptual Recapture of Gojihva (Onosma Bracteatum Wall.) - Swati Goyal,; Sudipta Rath,; Nitin Verma, (International Journal of Ayurveda and Pharma Research, 2022)
Aim: To collect and comprehensively review information available regarding the medicinal use of Gojihva. Background: Gojihva /Gowjaban is a very useful medicinal plant commonly used for fever, cough, bronchitis, rhinitis, stomatitis & weakness of cardiac muscles. This plant is used by Unani, Ayurveda and other traditional systems of medicine. A lot of research has also been conducted on this plant exploring its pharmacological utilization. Though there are few review articles available on this plant but no review has comprehensively covered all aspects of Gojihva. Materials and Methods: This review is in a narrative format and done from literature and publications relevant to Gojihva that were identified through a systematic search of major computerized medical databases. Conclusion: Gojihva is concluded to have more than 20 Samhita based indications -Aanushastra, Vistravan in Vran, Jihwa roga, Mukha Roga, Kushtha, Vran Ropan, Granthi Pralepa, Jwara, Sarpa Vish, Lutta Vish, Mushika, Vish Upadrava, Alarka Vish, Grahi, Hridya Roga, Kasa, Shwasa, Pratishyaya, Aaruchi, Prameha & Mutrakricha. Gojihva also possesses Analgesic Effect, Anti-Ageing Effect, Antioxidant Effect and Free Radical Scavenging Capacity, Antimicrobial /Anti-Leprotic Effect, Antifungal/Antibacterial Effect, Antidepressant /Anxiolytic Effect, Antidiarrheal/ Anti-Spasmodic Effect, Anti-Asthmatic/Anti- Inflammatory Effect, Anti-Cancerous Effect, Psycho-Immunomodulatory Effect, Acetyl-Cholinesterase Inhibitory Activity, Herbicidal Effect & Cardioprotective/Anti-Hypertensive Effect. Clinical significance: Samhita based indications of Gojihva are compared with Article concluded effect and then areas of further reseach are identified in drug Gojihva.